Susceptibility of Anopheles gambiae s.l. to the neonicotinoid insecticide clothianidin in eighteen sites located along the south–north transect of Benin - Steve Zinsou Hougbe; Arthur Sovi; Koffi Koumodji; Minassou Juvénal Ahouandjinou; Zul-kifl Affolabi; Linda Towakinou; Saïd Chitou; Andil Agbo-Ola; Filémon Tokponnon; David Mahouton Zoungbédji; Hermann Sagbohan; Casimir Kpanou; et al. (Tropical Medicine and Health, 2025)
Abstract Background The widespread resistance of malaria vectors to traditional neurotoxic insecticides has stimulated the search for new insecticide classes with novel modes of action. For that, the present study was designed to collect data on the susceptibility of field-collected Anopheles gambiae sensu lato (s.l.) to clothianidin, a neonicotinoid insecticide used in agriculture and that recently received WHO approval for use in indoor residual spraying. Methods An. gambiae s.l. were collected as larvae and pupae from 18 sites located along the south–north transect of Benin, and reared to adulthood. Female mosquitoes aged 2–5 days were exposed to clothianidin-impregnated papers (2% weight by volume (w/v) of SumiShield™ 50WG dissolved in distilled water). Due to the delayed action of clothianidin, mortality was daily recorded over 7 days. Polymerase chain reaction was used to assess the molecular species composition in the An. gambiae s.l. complex and the frequency of knockdown resistance (kdr) and insensitive acetylcholinesterase (Ace-1 R ) mutations. Results Mortality rates of field-collected An. gambiae s.l. were very high (≥98%) between 2- and 7-day post-exposure, indicating full susceptibility to clothianidin. Molecular species identification revealed the presence of An. coluzzii (53.7%), An. gambiae sensu stricto (s.s.) (42.5%), and An. arabiensis (3.8%) in the An. gambiae s.l. complex. kdr and Ace-1 R mean frequencies were 84% (95% CI 82–86) and 3% (95% CI 2–4) in An. coluzzii, and 88% (95% CI 87–90) and 4% (95% CI 3–6) in An. gambiae s.s., respectively. Conclusions Findings of the present study indicates that An. gambiae s.l. populations collected along the north–south transect of Benin remain susceptible to clothianidin. This broadens the portfolio of indoor residual spraying products that the national malaria control programme can deploy to better control pyrethroid-resistant populations of vectors.